In vitro and in vivo studies on the effect of a mitochondrial fusion promoter on Leydig cell integrity and function - Garza, Samuel; Sottas, Chantal; Gukasyan, Hovhannes J.; Papadopoulos, Vassilios (Frontiers in Toxicology, 2024)
Background: The interstitial testicular Leydig cells are responsible for the production of testosterone, which functionally deteriorate with normal aging. Decreased expression of mitochondrial steroidogenic interactome proteins and diminished mitochondrial function in aging Leydig cells suggest that mitochondrial dynamics play a role in maintaining adequate levels of testosterone. Optic atrophy 1 (OPA1) protein regulates mitochondrial dynamics and cristae formation in many cell types. Previous studies showed that increasing OPA1 expression in dysfunctional Leydig cells restored mitochondrial function and recovered androgen production to levels found in healthy Leydig cells. These findings suggested that mitochondrial dynamics may be a promising target to ameliorate diminished testosterone levels in aging males. Methods: We used twelve-month-old rats to explore the relationship between mitochondrial dynamics and Leydig cell function. Isolated Leydig cells from aged rats were treated ex vivo with the cell-permeable mitochondrial fusion promoter 4-Chloro-2-(1-(2-(2,4,6-trichlorophenyl)hydrazono)ethyl) phenol (mitochondrial fusion promoter M1), which enhances mitochondrial tubular network formation. In parallel, rats were treated with 2 mg/kg/day M1 for 6 weeks before Leydig cells were isolated. Results:Ex vivo M1-treated cells showed enhanced mitochondrial tubular network formation by transmission electron microscopy, enhanced Leydig cell mitochondrial integrity, improved mitochondrial function, and higher testosterone biosynthesis compared to controls. However, in vivo treatment of aged rats with M1 not only failed to re-establish testosterone levels to that of young rats, it also led to further reduction of testosterone levels and increased apoptosis, suggesting M1 toxicity in the testis. The in vivo M1 toxicity seemed to be tissue-specific, however. Conclusion: Promoting mitochondrial fusion may be one approach to enhancing cell health and wellbeing with aging, but more investigations are warranted. Our findings suggest that fusion promoters could potentially enhance the productivity of aged Leydig cells when carefully regulated.